Challenges and solutions in combining RP and SP data to value recreation - González-Sepúlveda, Juan Marcos, author; Loomis, John B., advisor (Colorado State University. Libraries, 2008)
Valuing resources that lack a market could be a complicated endeavor due to the lack of appropriate prices. Non-market valuation methods have been the tools used to compensate for this shortcoming in the process of incorporating such resources into the economic analysis. Without these methods we would overlook the importance that such goods and services have to society and bias the related policy recommendations we present as economists. This dissertation looks at joining two of the most commonly used non-market valuation methods, namely, the Travel Cost Model (TCM) and the Contingent Valuation Method (CVM), and their application to valuing recreation in El Yunque National Forest in Puerto Rico. The combination of TCM and CVM in a joint estimator allows us to test the consistency between the two methods and uncover potential issues that each may be suffering from. The study finds that the geographical limitations of the study can cause underestimation of willingness to pay when using TCM. Furthermore, it shows that CVM can suffer from the same sampling issues as TCM when the samples are collected on site. Besides pointing out these problems, this work presents alternative ways in which they can be addressed. Finally, we provide another example that imposing a common underlying utility can significantly improve the joint use of these models.
Keywords: contingent valuation; contingent valuation methods; joint estimation; on-site sampling; Puerto Rico; recreation; resource valuation; travel cost; travel cost model